Tourist attractions of partner Orange cities (France) and of Jarosław (Poland) - Dąbrowski, Janusz; Doktor, Marek; Działek, Anna (Geotourism/Geoturystyka)
In the article showed most interested tourist and attractions of Orange and Provence which became presented by the French national team of the Polish delegation within the framework of of the cooperation and the cultural of based on partnership cities Orange (France) and Jarosław (Poland). Described also most interested tourist objects of Jarosław against the background of the characterization of the natural environment.